Die Interaktion von Herrschern und Eliten in imperialen Ordnungen des Mittelalters - Drews, Wolfram (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2018)
At both the center and periphery of empire, patterns of access to imperial centers developed quite differently according to membership in different elite groups. The persistence of imperial systems may have depended on the successful maintenance of such options for access. This volume examines imperial orders from this perspective in Europe, the Middle East, India, and China, from late antiquity to the end of the Middle Ages.